Bioactivity and Structural Characterization of Soluble Dietary Fiber from Lyophyllum decastes - HE Shanshan, LIU Liping, LIU Yanfang, FENG Jie, WANG Guangqiang, WANG Wenhan, ZHANG Jinsong (Shipin Kexue)
Soluble dietary fiber (SDF) from edible mushrooms has good biological activity. In order to develop and utilize SDF from edible mushrooms, the present study determined the SDF contents in different edible mushrooms by sequential enzymatic hydrolysis. SDF-rich mushrooms were selected and evaluated for their in vitro antioxidant activity, nitrite adsorption capacity, in vitro glucose-lowering (glucose adsorption capacity, α-amylase inhibitory and α-glucosidase inhibitory activity) and lipid-lowering (cholesterol esterase, pancreatic lipase, and cholesterol micelle solubility inhibitory activity) activities. Finally, SDF from Lyophyllum decastes, which had the best overall bioactivity among all tested species, was selected for structural characteristic analysis. Monosaccharide analysis showed that SDF from L. decastes consisted of glucose, galactose, mannose and glucuronic acid. Fourier transform infrared (FTIR) spectroscopy showed that the SDF exhibited characteristic absorption peaks of polysaccharides. Scanning electron microscopy (SEM) showed that it possessed an obvious porous structure. The results of this study indicate that the SDF from L. decastes is an excellent ingredient for functional foods with hypoglycemic and hypolipidemic activity.